Table of Content - -, (Journal of Curriculum and Teaching Methodology, 2024)
Table of Content:1. The reality of using artificial intelligence applications in the educational process from the point of view of female educational rehabilitation students at Sohar UniversityMs. Fatma Khalfan Alabri2. Psychometric properties of a virtual science labs assessment questionnaire using confirmatory factor analysis and neural networks among middle school studentsMs. Ibtihal Zakaria Hafez, Ms. Sara Owidh Alosimi, Co-Prof. Fawaz Hassan Shehadeh3. The impact of the use of gamification on the development of creative thinking skills among students of the basic third grade in the subject of Science in the capital AmmanMs. Huda Gumaa Al-Nadi4. The Effectiveness of a Developed Interactive Electronic Unit Based on the Green Economy in Social Studies for Enhancing Achievement of  Second Year Middle School Female  Students and Their Attitudes Towards ItDr. Hessa Abdullah Al-Enazi , Prof. Yousif Abdulrahman Alshumaimeri5. The degree to which Quality Matters standards are met in the "Madrasati Platform" e-learning management system from the perspective of secondaryMs. Majida Abdullah Alanazi, Ms. Nada Nasser Alqahtani6. Using Raz-kids Reading Program to Enhance Fifth Grade EFL Omani Students’ Reading Comprehension Skills and Boost their MotivationMs. Zahra Suleiman Saif Al-Riyami, Ms. Salama Saif Hamed Al-Siyabi
Keywords: Journal of Curriculum and Teaching Methodology